Radiological imaging finding of calcified pseudoneoplasm of neural axis - Singh, Aishwerya; Kumar, Deepak; Prasad, Umakant (Nepal Journal of Neuroscience, 2020)
Calcified pseudoneoplasm of neural axis (CAPNON) is rare non-neoplastic non-inflammatory heavily calcified lesions of neural axis which can be intra-parenchymal or extra-axial and have been reported within brain and spinal cord with equal frequency. Here we describe unique radiological (CT &MRI) Imaging finding of CAPNON in left hippocampus on CT scan and MRI.